2016
DOI: 10.1016/j.jadohealth.2015.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Cyberbullying Prevalence Among US Middle and High School–Aged Adolescents: A Systematic Review and Quality Assessment

Abstract: Background Cyberbullying has established links to physical and mental health problems including depression, suicidality, substance use, and somatic symptoms. Quality reporting of cyberbullying prevalence is essential to guide evidence-based policy and prevention priorities. The purpose of this systematic review was to investigate study quality and reported prevalence among cyberbullying research studies conducted in populations of US adolescents of middle and high school age. Methods Searches of peer-reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
108
2
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(145 citation statements)
references
References 93 publications
(85 reference statements)
10
108
2
10
Order By: Relevance
“…Aside from the Albdour and Krouse review, however, reviews of bullying and cyberbullying research are problematic in that they tend to exclude research that focuses on youth of color (Selkie et al, 2015), struggle to find studies about youth of color (Hamm et al, 2015) or simply fail to report findings about youth of color in their review (Kowalski et al, 2014). Hamm et al (2015) explored the frequency and impact of cyberbullying on youth in 36 studies that focused on health-related effects of cyberbullying.…”
Section: Mental Health Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Aside from the Albdour and Krouse review, however, reviews of bullying and cyberbullying research are problematic in that they tend to exclude research that focuses on youth of color (Selkie et al, 2015), struggle to find studies about youth of color (Hamm et al, 2015) or simply fail to report findings about youth of color in their review (Kowalski et al, 2014). Hamm et al (2015) explored the frequency and impact of cyberbullying on youth in 36 studies that focused on health-related effects of cyberbullying.…”
Section: Mental Health Effectsmentioning
confidence: 99%
“…In their review of 81 cyberbullying studies, Selkie, Fales and Moreno (2015) intentionally excluded research that focused solely on "special populations", such as students with disabilities or who identified as lesbian, gay, bisexual, transgender queer/questioning (LGBTQ). Although the authors did not specifically mention race or ethnicity as a special population, they also did not report findings about members of these communities, either as specific populations or sample subgroups within the general samples.…”
Section: Mental Health Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many disciplines already working to understand bullying or the related constructs. Outside of psychology, these include criminal justice (e.g., Patchin 2011), communications (Vandebosch andVan Cleemput 2009), medicine (Selkie et al 2015) and computer science . Criminal justice approaches have clear relevance for distinguishing bullying from workplace bullying, dating aggression, harassment, delinquency, and offending behavior.…”
Section: Discussionmentioning
confidence: 99%
“…This survey included both traditional bullying and cyberbullying. In another study, the range of reported cyberbullying was perpetration, 1-41%; victimization, 3-72%; and overlapping perpetration and victimization, 2.3-16.7% [12]. These numbers likely underestimate the scope of problem, as most children keep silent to these experiences for a number of reasons including fear and embarrassment [13].…”
Section: Introductionmentioning
confidence: 99%